Examination of Patients’ Attitudes Toward Exercising Patient Rights in a University Hospital in turkey: A Cross-Sectional Study - Can Özdemir, Rana; Tambağ, Hatice (SAGE open, 2023)
Patient rights support patient autonomy and is an important bioethics issue that has been on the healthcare agenda in recent decades. Patients exercising their rights is one of the factors that positively affect the care and treatment process. The aim of this study is to determine the attitudes toward patients exercising their rights, factors affecting it, and to raise awareness on the subject. This cross-sectional descriptive study was conducted with 421 patients hospitalized in a university hospital in Turkey. Data were collected using the Scale of Patient Rights Using Attitude (SPRUA) and 16 questions identifying the demographic characteristics of the participants and information that is thought to affect attitudes toward patient rights. Each statement on the SPRUA, a Likert-type scale, is scored from 5 to 1. The total score that can be obtained from the scale ranges between 29 and 145. The total score on the scale determines the attitude toward using patient rights. The Shaphiro wilk test, Student t test, One Way ANOVA, Tukey multiple comparison tests, Kruskal Wallis and All pairwise tests were used to evaluate the data. Participants’ total mean score on the SPRUA was 117.50 ± 22.72. Some socio-demographic variables and experiences during the illness affected the participants’ attitudes toward exercising patient rights. There was a significant difference between the participants’ the mean SPRUA score and the following factors: age, education level, place of residence, clinic hospitalized in, chronic disease status, knowledge about patient rights, duration of hospitalization. The participants had high mean scores on the scale.